6th European Pulse Plating Seminar. (July 2014) - Zanella, C.; Leisner, P.
<x content-type="archive" xml:space="preserve">Abstract</x> Over the past decade the European Pulse Plating Seminar has been established as the most important event for discussing research and applications of pulse plating. Now it is organised every second year in the area of Vienna by the company Happy Plating. For the past two years it has been co-organised with the European Academy of Surface Technology, EAST. The pulse plating seminars have made it possible to follow how the application of pulse plating has increased and widened during the last decade since the first seminar in 2006.